2008
DOI: 10.1002/jnr.21717
|View full text |Cite
|
Sign up to set email alerts
|

The growth‐inhibitory protein Nogo is involved in midline routing of axons in the mouse optic chiasm

Abstract: We have investigated the role of Nogo, a protein that inhibits regenerating axons in the adult central nervous system, on axon guidance in the developing optic chiasm of mouse embryos. Nogo protein is expressed by radial glia in the midline within the optic chiasm where uncrossed axons turn, and the Nogo receptor (NgR) is expressed on retinal neurites and growth cones. In vitro neurite outgrowth from both dorsonasal and ventrotemporal retina was inhibited by Nogo protein, and this inhibition was abolished by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…Factors that limit axon outgrowth and plasticity have been purified from CNS myelin and include myelin associated glycoprotein (MAG), oligodendrocyte myelin glycoprotein (OMgp), and NogoA (McGee et al, 2005; Walmsley and Mir, 2007; Giger et al, 2008; Gonzenbach and Schwab, 2008). In addition to limiting axon outgrowth and plasticity in the adult CNS, NogoA also regulates axon outgrowth and plasticity during development (Petrinovic et al, 2010; McGee et al, 2005; Syken et al, 2006; Mingorance-Le Meur et al, 2007; Atwal et al, 2008; Wang et al, 2008; Brosamle and Halpern, 2009; Datwani et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Factors that limit axon outgrowth and plasticity have been purified from CNS myelin and include myelin associated glycoprotein (MAG), oligodendrocyte myelin glycoprotein (OMgp), and NogoA (McGee et al, 2005; Walmsley and Mir, 2007; Giger et al, 2008; Gonzenbach and Schwab, 2008). In addition to limiting axon outgrowth and plasticity in the adult CNS, NogoA also regulates axon outgrowth and plasticity during development (Petrinovic et al, 2010; McGee et al, 2005; Syken et al, 2006; Mingorance-Le Meur et al, 2007; Atwal et al, 2008; Wang et al, 2008; Brosamle and Halpern, 2009; Datwani et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…For instance, the Nogo-A, expressed by radial glia repulse optic nerve axons in the optic chiasm, is shown to restrict the axons to grow through the interaction between Nogo-66 and NgR1 [73]. In addition, Nogo-A might participate in the repulsion of spinal cord commissural axons at ventral midline [74].…”
Section: Migration and Distributionmentioning
confidence: 99%
“…CF terminals observed in P28 Nogo-A KO PCs points to a hyperinnervation derived from a single inferior olive axon. In the meantime, the synaptic strength of the parallel fiber-Purkinje cell (PF-PC) synapses improved in A decrease in acetylated a-tubulin at the tips of neurites for primary neurons; redistribution of acetylated a-tubulin in HEK293FT cell lines [72] Young postnatal brain Nogo-A ablation or neutralization or its virusmediated down-regulation Increased blood vessel density and the number of endothelial tip cells [55] Postnatal Retina Nogo-A ablation or neutralization Increased tissue density of blood vessels [55] Cultured MVECs in vitro Treatment with Nogo-A-specific fragment D20 or with either P10 WT or P10 Nogo-A -/-brain membrane protein extract Inhibition on cell spreading and adhesion of MVECs by Nogo-A D20 in a dose-dependent manner [55] Cultured dorsal root ganglion neurons Nogo-A ablation or neutralization Longer neurites, increased fasciculation, and decreased branching of cultured dorsal root ganglion neurons [73] In the chicken embryo Injection of anti-Nogo-A antibodies or Genetic ablation of Nogo-A Aberrant innervation of the hindlimb or increased fasciculation and reduced branching of peripheral nerves [73] Dorsonasal and ventrotemporal retina Treatment with Nogo protein In vitro Inhibition on neurite outgrowth from both dorsonasal and ventrotemporal retina [74] Spinal cord of mouse embryos…”
Section: Modulation Of Synaptic Plasticitymentioning
confidence: 99%
“…Chan SunOn and colleagues discovered a novel developmental function of Nogo, an inhibitory molecule for axon regeneration in the adult central nervous system [7], in the sorting of VT retinal axons into the ipsilateral projection [29,30]. They observed that Nogo is expressed by radial glia in the midline within the optic chiasm, and the Nogo receptor (NgR) is expressed in retinal neurites and growth cones.…”
Section: Guidance Of Retinal Axons In the Optic Chiasm By Other Proteinsmentioning
confidence: 99%